First record of stone moroko (Pseudorasbora parva), an invasive alien fish species, in water bodies of urban green areas in Poland - Wróblewski Paweł; Maciaszek Rafał; Kasprzak Robert (Fisheries & Aquatic Life)
Invasive alien species are currently a major ecological problem. One such species is stone moroko, Pseudorasbora parva (Gobionidae), which has only been found to date in natural or agricultural water bodies (lakes, rivers and streams, carp ponds). Therefore, the current study is the first description of stone moroko in urban green areas (Warsaw, Poland). The fish were caught with a hydrobiological net. Four catches were conducted in ponds located in Morskie Oko Park (pond 1) and the Saxon Garden (pond 2) – two in fall and two in the spring, while two spring catches were conducted in Dolinka Służewska Park (stream). The population in pond 2 apparently survived the winter, and the fish caught in June displayed visible signs of sexual dimorphism and were significantly larger (average body mass: 1648 ± 1123 mg; range: 460–6090 mg) than those caught in the pond in the two fall samplings (404 ± 122 mg; 154–729 mg). After recording substantial numbers of specimens in the fall, no fish were caught in pond 1 during either of the spring catches, while only a few moroko were caught in the stream in April (1212 ± 869 mg; 454–2901 mg) and none were caught in June. Throughout the study, 59 specimens were caught in pond 1, 74 in pond 2, and 7 in the stream.